Continuous recycling of enzymes during production of lignocellulosic bioethanol in demonstration scale. (1st December 2015) - Haven, Mai Østergaard; Lindedam, Jane; Jeppesen, Martin Dan; Elleskov, Michael; Rodrigues, Ana Cristina; Gama, Miguel; Jørgensen, Henning; Felby, Claus
Highlights: Results from continuous experiments in demonstration scale for a total of 16 days. Reuse of enzymes is possible through recycling fermentation broth. Recycling fermentation broth can increase ethanol concentration with lower dry matter. Abstract: Recycling of enzymes in production of lignocellulosic bioethanol has been tried for more than 30 years. So far, the successes have been few and the experiments have been carried out at conditions far from those in an industrially feasible process. Here we have tested continuous enzyme recycling at demonstration scale using industrial process conditions (high dry matter content and low enzyme dosage) for a period of eight days. The experiment was performed at the Inbicon demonstration plant (Kalundborg, Denmark) capable of converting four tonnes of wheat straw per hour. 20% of the fermentation broth was recycled to the hydrolysis reactor while enzyme dosage was reduced by 5%. The results demonstrate that recycling enzymes by this method can reduce overall enzyme consumption and may also increase the ethanol concentrations in the fermentation broth. Our results further show that recycling fermentation broth also opens up the possibility of lowering the dry matter content in hydrolysis and fermentation while still maintaining high ethanol concentrations.